Singapore in Malaysia: An Examination of Argument Structures in a Malaysian History Textbook - David Yoong; Kumaran Rajandran; Rubini Devi Suppiramaniam (Kajian Malaysia, 2017)
The article explores how the Malaysian Form 3 history textbook portrays Singapore's merger and separation. The portrayal can influence the perception of Singapore among Malaysians. Singapore was part of Malaysia for about two years (1963–1965) and its brief union represents a crucial historical episode. The episode is analysed using Toulmin's argument structures. The analysis identifies the claims, grounds and warrants for the arguments, and it also examines the use of lexicogrammatical and intertextual features. Certain arguments articulate the benefits of the merger and it is endorsed by foreign and local leaders, and the general population. Subsequently, other arguments articulate the threats which Singapore posed and its separation is made to seem inevitable. The textbook portrays Singapore as an enthusiastic partner and later a distrusted partner of the Malaysian Federal Government. Its arguments validate the state-sanctioned version of history. The article also provides four proposals to improve history textbooks.